Recurrent Adult Choroid Plexus Carcinoma Treated with High-Dose Chemotherapy and Syngeneic Stem Cell (Bone Marrow) Transplant - Samuel, Thomas A.; Parikh, Jigarkumar; Sharma, Suash; Giller, Cole A.; Sterling, Kristen; Kapoor, Suraj; Pirkle, Christen; Jillella, Anand (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Choroid plexus carcinomas (CPCs) are rare epithelial central nervous system tumors. CPC occurs mainly in infants and young children, comprising ∼1 to 4% of all pediatric brain neoplasms. There is very limited information available regarding tumor biology and CPC treatment due to its rarity. There have been various case reports and meta-analyses of reported cases with CPC. Surgical resection is often challenging but remains a well-established treatment option. Chemotherapy is often reserved for recurrent or refractory cases, but the goal of treatment is usually palliative. We present a case of recurrent, adult CPC with disseminated leptomeningeal involvement treated with salvage chemotherapy including high-dose ifosfamide, carboplatin, and etoposide; once a remission was achieved, this response was consolidated with a syngeneic stem cell (bone marrow) transplant after a preparative regimen of high-dose chemotherapy with carboplatin, etoposide, and thiotepa. Although the patient tolerated the transplant well and remained disease-free for 12 months, she subsequently succumbed to relapsed disease 18 months posttransplant. We believe that this is the first report of using syngeneic stem cell transplant in CPC to consolidate a remission achieved by salvage chemotherapy.
Keywords: choroid; carcinoma; transplant; chemotherapy